1999
DOI: 10.1002/1531-8249(199902)45:2<154::aid-ana4>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular levels of the LIS1 protein correlate with clinical and neuroradiological findings in patients with classical lissencephaly

Abstract: We report on the genotype–phenotype correlation in 7 patients with classical lissencephaly carrying a heterozygous subtle mutation in the LIS1 gene. Six patients showed a mutation predicted to encode for a truncated protein, and one mutation altered a splicing site, resulting in skipping of exon 4. Western blot analysis performed on the lymphoblastoid cell line of 2 patients bearing truncating mutations indicated that the mutated allele did not produce a detectable amount of the LIS1 protein; whereas the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…8 Indeed, just as our analysis detects partial protein synthesis from the mutated allele, a similar partial protein was detected in this specific patient. 8 Therefore, in the case of this mutation, it appears that the cells contain more LIS1 protein, normal amounts of the wild type protein resulting from the normal allele and in addition the sLIS1 product from the mutated allele. Compared to classic lissencephaly, 5 the N-terminal deletion patient showed a less severe degree of cortical abnormality including no seizures.…”
Section: Lis1 Function In Developmentsupporting
confidence: 63%
See 2 more Smart Citations
“…8 Indeed, just as our analysis detects partial protein synthesis from the mutated allele, a similar partial protein was detected in this specific patient. 8 Therefore, in the case of this mutation, it appears that the cells contain more LIS1 protein, normal amounts of the wild type protein resulting from the normal allele and in addition the sLIS1 product from the mutated allele. Compared to classic lissencephaly, 5 the N-terminal deletion patient showed a less severe degree of cortical abnormality including no seizures.…”
Section: Lis1 Function In Developmentsupporting
confidence: 63%
“…5 The mutation we generated resembles that of a patient with an in-frame N-terminal deletion. 8 Indeed, just as our analysis detects partial protein synthesis from the mutated allele, a similar partial protein was detected in this specific patient. 8 Therefore, in the case of this mutation, it appears that the cells contain more LIS1 protein, normal amounts of the wild type protein resulting from the normal allele and in addition the sLIS1 product from the mutated allele.…”
Section: Lis1 Function In Developmentsupporting
confidence: 59%
See 1 more Smart Citation
“…Our previous analysis indicated that truncated or internally deleted LIS1 protein is unlikely to fold correctly (11). This finding was supported by a study done in cells derived from lissencephaly patients, where no protein was detected from mutated alleles that were expected to result in a truncated protein (12). The five patients with point mutations that lead to a single amino acid substitution in LIS1 exhibit a variable phenotypic manifestation.…”
mentioning
confidence: 60%
“…58 Neurons are the most sensitive cells to the loss of LIS1 protein activity and decrease in LIS1 amount. 59 On the other hand, NUDEL, LIS1-interacting regulator of various types of dynein activities, including membranous organelle trafficking, 18,60 is important for assembly and transport of neurofilaments; NUDEL deficiency leading to neurodegeneration. 61 The titration of LIS1 by protein 3A could be one of the possible reasons of poliovirus induced neuronal disorder.…”
Section: Discussionmentioning
confidence: 99%